2018
DOI: 10.1080/15592294.2018.1543504
|View full text |Cite
|
Sign up to set email alerts
|

The proto CpG island methylator phenotype of sessile serrated adenomas/polyps

Abstract: Sessile serrated adenomas/polyps (SSA/Ps) are the putative precursors of the ~20% of colon cancers with the CpG island methylator phenotype (CIMP). To investigate the epigenetic phenotype of these precancers, we prospectively collected fresh-tissue samples of 17 SSA/Ps and 15 conventional adenomas (cADNs), each with a matched sample of normal mucosa. Their DNA was subjected to bisulfite next-generation sequencing to assess methylation levels at ~2.7 million CpGs located predominantly in gene regulatory regions… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
66
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(72 citation statements)
references
References 85 publications
(109 reference statements)
6
66
0
Order By: Relevance
“…RNA-based gene expression pro les obtained in previous studies by our group have revealed numerous RNA markers that are differentially expressed in SSA/Ps and cADNs [28]. Here, using ISH, we veri ed the accuracy of 9 of the 12 markers putatively capable of distinguishing between these two major premalignant tumor types.…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…RNA-based gene expression pro les obtained in previous studies by our group have revealed numerous RNA markers that are differentially expressed in SSA/Ps and cADNs [28]. Here, using ISH, we veri ed the accuracy of 9 of the 12 markers putatively capable of distinguishing between these two major premalignant tumor types.…”
Section: Discussionmentioning
confidence: 57%
“…In each section, staining of the normal mucosal crypts at the border of each lesion was assessed as an internal normal-tissue control. The choice of the RNA targets to be veri ed was based on RNA-sequencing data on precancerous colorectal lesions previously published by our group [28] (Supplementary Fig. 2) and others [45] ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations